Predictors of persistent postoperative pain after surgery for idiopathic scoliosis. (2021) - Charalampidis, Anastasios; Rundberg, Lina; Möller, Hans; Gerdhem, Paul
Abstract: Purpose: To identify factors contributing to persistent postoperative pain in patients treated surgically for idiopathic scoliosis. Methods: In total, 280 patients aged ten through 25 years at surgery, were identified in the Swedish Spine registry; all having preoperative and postoperative visual analogue scale (VAS) for back pain scores. The patients were divided into a high and low postoperative pain group based on the reported postoperative VAS for back pain scores (by using 45 mm on the 0 mm to 100 mm VAS scale as a cut-off). The patient-reported questionnaire included VAS for back pain, the 3-level version of EuroQol 5-dimensional (EQ-5D-3L) instrument, the EuroQol VAS (EQ-VAS) and the Scoliosis Research Society 22r instrument (SRS-22r). Predictors of postoperative back pain were searched in the preoperative data. Results: The 67 (24%) patients that reported high postoperative VAS back pain (> 45 mm) also reported lower postoperative EQ-5D-3L, EQ-VAS and SRS-22r than patients with low postoperative VAS back pain (all p < 0.001). Two preoperative variables were independently associated with postoperative pain; each millimetre increase in preoperative VAS back pain (on the 0 mm to 100 mm scale) was associated with a higher risk of being in the high postoperative back pain group (odds ratio (OR) 1.03; 95% confidence interval (CI) 1.02 to 1.05) and each 1 point decrease on the preoperative SRS-22r mental health (scale from 1 to 5) was associated with a higher risk of being in the high postoperative back pain group (OR 1.68; 95% CI 1.03 to 2.73). Conclusion: High preoperative back pain and low preoperative mental health are independent predictors of back pain after surgery for idiopathic scoliosis. Level of Evidence: III